HEGEMONIC MASCULINITY: Wacana Relasi Gender dalam Tinjauan Psikologi Sosial - Oktarizal Drianus; Rusdian Dinata; Diah Meitikasari (Department of Islamic Psychology, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
Today, the world is languishing in a patriarchal structure. This patriarchal domination not only harms women, but also men, children, the elderly, and marginalized groups. Gender mainstreaming extends its studies not only to femininity but to parenting (motherhood and fatherhood), early childhood. In addition, gender also extends to the realm of masculinity or male studies. In this case, the psychology of gender underlines this phenomenon with hegemonic masculinity discourse. Masculinity is seen from the dominance of the spaces of life both public and private. This paper examines the ideology of hegemonic masculinity as the most desirable theoretical response to Critical Men Studies (CSM). This elaboration of the Hegemonic Masculinity concept is useful as a 'binocular tool' that is operational for empirical studies of masculinity.